Reshaping the Global Climate Change Regime through the Paris Agreement - Okonkwo, Theodore (Christ University Law Journal, 2017)
The Paris Agreement on Climate Change which aimed at halting climate change and limiting global warming to 1.5 degrees Celsius, remains the most important piece of international diplomacy in years, since the Kyoto Protocol of 1992 and the Copenhagen Accord (which endorsed the continuation of the Kyoto Protocol) 2009. The signing of the Paris Agreement underlies the fact that climate change remains one of the greatest challenges of our time and calls for a strong political will to urgently combat climate change in accordance with the principle of common but differentiated responsibilities and respective capabilities. This article looks at Paris Agreement’s resolve to peak global greenhouse-gas emissions as soon as possible and also undertakes a cursory examination of the global climate regime. The article also examines how the problem of climate change has altered since the 2009 Copenhagen Accord and concludes by emphasizing the need to take the Paris Agreement forward in spirit.